2022
DOI: 10.18805/ijar.b-4406
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-haematobiochemical Evaluation of Diaphragmatic Hernia and its Surgical Management in Cattle and Buffaloes-A Retrospective Study of 32 Cases

Abstract: Background: Diaphragmatic hernia is an emerging threat in dairy animals due to accidental ingestion of potential foreign body via feed or fodder leads to traumatic reticulo pericarditis and net results into loss of milk production. Loss of milk production due to diaphragmatic hernia in dairy animals is worrying situation among the milkman and it needs to be addressed in early stage. Considering the livelihood of poor to marginal farmers on dairy animals, the present study aimed to evaluate the clinico-haematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Significantly elevated total leucocytes with neutrophilia and total protein is a consistent finding on bovines positive for DH (Kaur and Singh, 1994;Rose et al, 2009;Abdelaal et al, 2014;Attia, 2016;Ghanshym et al, 2020) irrespective to the presence of foreign body, which was correlated to the destruction of lymphocytes due to stress (Jain, 1986) tissue damage and suppuration at the site of injury (Kaur and Singh, 1994). The SGOT, Creatinine Kinase and Serum Creatinine (Ghanshym et al, 2020, Suryawanshi et al 2023 are significantly high and SGPT to be significantly low in DH buffaloes as compared to normal (Kaur and Singh, 1994;Rose et al, 2009). DH may cause reduced serum total bilirubin, AST, BUN, creatinine glucose, lactate and fbrinogen in buffaloes (Hussain et al, 2021).…”
Section: Hemato-biochemistrymentioning
confidence: 78%
See 1 more Smart Citation
“…Significantly elevated total leucocytes with neutrophilia and total protein is a consistent finding on bovines positive for DH (Kaur and Singh, 1994;Rose et al, 2009;Abdelaal et al, 2014;Attia, 2016;Ghanshym et al, 2020) irrespective to the presence of foreign body, which was correlated to the destruction of lymphocytes due to stress (Jain, 1986) tissue damage and suppuration at the site of injury (Kaur and Singh, 1994). The SGOT, Creatinine Kinase and Serum Creatinine (Ghanshym et al, 2020, Suryawanshi et al 2023 are significantly high and SGPT to be significantly low in DH buffaloes as compared to normal (Kaur and Singh, 1994;Rose et al, 2009). DH may cause reduced serum total bilirubin, AST, BUN, creatinine glucose, lactate and fbrinogen in buffaloes (Hussain et al, 2021).…”
Section: Hemato-biochemistrymentioning
confidence: 78%
“…DH is rarely reported in cows/cattle (Dollar, 1895;Milne, 1951;Hall, 1963;Deshpande et al, 1977;Saini et al, 2007;Sharma et al, 2024). However, a latest report showed an equal occurrence of DH in cattle and buffaloes (Suryawanshi et al 2023). DH in a buffalo has been earliest documented in an MVSc thesis from Bombay Veterinary College, India (Deshpande, 1965), where it was an incidental finding during laparo-rumenotmy.…”
Section: An Updated Review On the Diaphragmatic Hernia In Bovinesmentioning
confidence: 99%
“…Saini et al (2000) reported case studies on buffaloes that did not survive during the recovery period treatment of DH. Suryawanshi et al , 2023 outlined the absorption of a foreign body through feed or fodder, which causes traumatic reticulopericarditis and ultimately reduces milk supply. Asrat and Velappa, 2016 highlighted that adult calves commonly experience several forestomach problems, including traumatic reticuloperitonitis, ruminal acidosis and bloat, as well as surgical remedies such as rumenotomies and DH surgery.…”
Section: Introductionmentioning
confidence: 99%